Artificial Intelligence (AI) In Malaysian Schools: A Scoping Review Of Teacher Readiness And Implementation Challenges (2020–2025) - Rosmalily Salleh; Vaikunthan Rajaratnam; Shahazwan Mat Yusoff; Saedah Siraj (The International Journal of Education Management and Sociology, 2026)
The rapid advancement of Artificial Intelligence (AI) is reshaping educational systems globally, raising pressing questions about implementation readiness, governance, and professional capacity. In line with the implementation of the Digital Education Policy by the Ministry of Education Malaysia, there is an increasing need to understand AI implementation readiness and the challenges associated with AI integration in schools. This study aims to map and synthesise existing literature on AI implementation readiness and related issues in Malaysian national schools between 2020 and 2025. A scoping review methodology guided by the PRISMA-ScR framework was employed. Literature was sourced from MyJurnal, Google Scholar, and ERIC databases. Thematic analysis identified three dominant themes: high levels of teacher interest accompanied by moderate technical competence, significant infrastructural disparities between urban and rural schools, and the absence of clear ethical guidelines governing AI use in classrooms. The findings indicate that while Malaysian teachers demonstrate positive attitudes towards the potential of AI to enhance learning, systematic support in terms of professional development, infrastructure, and policy remains insufficient.